2011
DOI: 10.5194/bg-8-89-2011
|View full text |Cite
|
Sign up to set email alerts
|

Tracing the origin of dissolved silicon transferred from various soil-plant systems towards rivers: a review

Abstract: Abstract. Silicon (Si) released as H 4 SiO 4 by weathering of Si-containing solid phases is partly recycled through vegetation before its land-to-rivers transfer. By accumulating in terrestrial plants to a similar extent as some major macronutrients (0

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
143
1
4

Year Published

2011
2011
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 249 publications
(161 citation statements)
references
References 205 publications
(322 reference statements)
6
143
1
4
Order By: Relevance
“…Nevertheless, variations in CSi a with depth in continuously forested ecosystems did not reflect variations of soil OC with depth. Several factors such as a varying phytolith input of roots with depth (Gill and Jackson, 2000), vertical translocation of phytoliths (Alexandre et al, 1997;Meunier et al, 1999), variations in silica solubility or (re-) precipitation of pedogenic silica (Cornelis et al, 2011b) with depth could all contribute to the observed ASi distribution. Our data do not allow to identify the relative contribution of each of these processes.…”
Section: Amorphous Silica and Organic Carbonmentioning
confidence: 99%
“…Nevertheless, variations in CSi a with depth in continuously forested ecosystems did not reflect variations of soil OC with depth. Several factors such as a varying phytolith input of roots with depth (Gill and Jackson, 2000), vertical translocation of phytoliths (Alexandre et al, 1997;Meunier et al, 1999), variations in silica solubility or (re-) precipitation of pedogenic silica (Cornelis et al, 2011b) with depth could all contribute to the observed ASi distribution. Our data do not allow to identify the relative contribution of each of these processes.…”
Section: Amorphous Silica and Organic Carbonmentioning
confidence: 99%
“…The Si fluxes recycled by plants are substantial; for example, Si take up by tropical forests or grasslands can reach 2 to 10 times Si fluxes generated from the dissolution of soil silicates that are exported to stream water (e.g., Blecker et al, 2006;Struyf and Conley, 2009;Cornelis et al, 2011;Alexandre et al, 2011). Inside the plant, Si is transported in the sap and deposited inside the cells, in the cell walls and in extracellular spaces of stems and leaves as micrometric hydrous amorphous silica particles called phytoliths.…”
Section: Introductionmentioning
confidence: 99%
“…Earlier studies have hypothesized that volcanic glass shards substantially contribute to measured Si Alk (Cornelis et al, 2011b;Lyle and Lyle, 2002;Sauer et al, 2006). In the following, we discuss the specific dissolution characteristics of glass shards, during alkaline extraction and implications for soil and palaeoecological studies.…”
Section: Discussionmentioning
confidence: 99%
“…Cornelis et al (2011b) reviewed sources that may completely dissolve and find that in addition to biogenic remains (e.g. phytoliths, diatoms), inorganic forms such as Al-Si precipitates, volcanic glass shards, adsorbed Si on amorphous iron oxides, and nanocrystalline fractions such as allophanes and imogolite can comprise a substantial portion of the nonlinearly dissolving Si.…”
Section: Introductionmentioning
confidence: 99%